Acute Kidney Injury Following Usage of Formaldehyde-Free Hair Straightening Products (Iranian Journal of Kidney Diseases, 2019)
Acute kidney injury is manifested by sudden deterioration of kidney functions, with or without reduction of urine output. The spectrum of injury ranges from mild to severe, sometimes requires renal replacement therapy. The initial workup includes a patient history to identify the use of nephrotoxic medications or systemic illnesses that may cause poor renal perfusion or directly impair renal function. Formaldehyde which present in cosmetic products; is toxic to many parts including respiratory, renal, and neurologic systems. Here, we have reported 2 cases of acute kidney injury (AKI) after using formaldehyde free hair straightening protein presented with acute tubular injury, responded to corticosteroid therapy.